Tinea corporis by Microsporum audouinii in a female chimpanzee (Pan troglodytes) from Guinea‐Bissau: A case report. Issue 6 (24th August 2018) - Melo, Pedro; Lança, Anabela; Mané, Braima Amadeu; Regalla, Aissa; Ferreira da Silva, Maria Joana; Tavares, Luis; Bernardo, Fernando; Oliveira, Manuela
Abstract: We report a Microsporum audouinii infection in a female juvenile chimpanzee ( Pan troglodytes ) presenting generalized dermatitis compatible with dermatophytosis. Dermatophyte was identified by macro‐ and microscopic characterization of skin and scales cultures in Mycosel Agar. The topical treatment applied was effective, having the potential for dermatophytosis treatment in immunocompetent primates.